"There is no out there": trans-corporeality and process philosophy in Muriel Rukeyser's The Speed of Darkness. Issue 2 (3rd May 2020) - Daw, Sarah
ABSTRACT: Drawing extensively on Muriel Rukeyser's archived notes, this essay reveals that Alfred North Whitehead's "philosophy of organism" influences and shapes the experimental poetics that Rukeyser outlines in The Life of Poetry (1949). The "process" ecopoetics debuted in The Life of Poetry also facilitates Rukeyser's radical reimagination of the human subject as dynamically entangled with an agential environment in her much-overlooked 1969 poetry collection, The Speed of Darkness . Establishing Whitehead as a major influence on Rukeyser's ecopoetics makes a new case for her work's significance to current material ecocritical debates and affirms her legacy and influence within contemporary ecopoetry.